Od „Przeglądu Archeologicznego” do Karola Hadaczka: archeologia lwowska w latach 1876-1914 - Bulyk, Natalia (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2006)
This paper is dedicated to history of foundation of Lviv archaeological center in 19th century. The main stages of history of some institutions, which works with archaeological themes and carried out archaeological researches, are described. End of 19th - beginning of 20th century can be characterized as a time of formation of Lviv archaeological centre. Such archaeological institutions as Regional Archaeological Society, Shevchenko Scientific Society, Stavropigia Institute and Lviv University carried out archaeological researches professionally. So, it is necessary to analyze activity of these institutions
ill. ; 29 cm
Keywords: Ukraine; Lviv; history of archaeology; University of Lviv; Regional Archaeological Society (Lemberg); Shevchenko Scientific Society; Stavropigia Institute; “Przegląd Archeologiczny”; chair of classical archaeology and prehistory; Karol Hadaczek (1873-1914); Ukrainian-Polish relations